129k views
2 votes
Plzzz answer this.... Its very important ​

Plzzz answer this.... Its very important ​-example-1
User Aykut
by
5.5k points

2 Answers

5 votes

Answer:

y = 1.65

x = 2.32

Explanation:


1)(5)/(y) - (2)/(x) = (13)/(6) == -(36)/(x) + (90)/(y) = (234)/(6) \\2)(36)/(x) - (24)/(y) = 1

Adding 1) + 2)


(66)/(y) = (240)/(6) \\ y = (33)/(20)\\ x = (44)/(19)

User Ramana V V K
by
5.5k points
4 votes

Answer:

x = 44/19, y = 33/20

Explanation:

Multiply the first eq by 18, to get:

90/y - 36/x = 39

so 36/x = 90/y - 39

in this form we can plug it into the second eq:

90/y - 39 - 24/y = 1 =>

66/y = 40 =>

y = 66/40 = 33/20

Fill that in the first:

100/33 - 2/x = 13/6 =>

200/66 - 143/66 = 2/x =>

57/66 = 2/x =>

57x = 2*66

x = 132/57 = 44/19

User WhatisSober
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.